Time-resolved observations of vibrationally excited NO X 2Π (v′) formed from collisional quenching of NO A 2Σ+ (v = 0) by NO X 2Π: evidence for the participation of the NO a 4Π state. Issue 36 (9th September 2021) - Fletcher, James D.; Lanfri, Lucia; Ritchie, Grant A. D.; Hancock, Gus; Islam, Meez; Richmond, Graham
Abstract : Time resolved observations of the products of NO A 2 Σ + collisional quenching show fast and slow components, consistent with the involvement of a reservoir state (a 4 Π) through which a portion of the quenching occurs. Abstract : Time-resolved observations have been made of the formation of vibrationally excited NO X 2 Π ( v ′) following collisional quenching of NO A 2 Σ + ( v = 0) by NO X 2 Π ( v = 0). Two time scales are observed, namely a fast production rate consistent with direct formation from the quenching of the electronically excited NO A state, together with a slow component, the magnitude and rate of formation of which depend upon NO pressure. A reservoir state formed by quenching of NO A 2 Σ + ( v = 0) is invoked to explain the observations, and the available evidence points to this state being the first electronically excited state of NO, a 4 Π. The rate constant for quenching of the a 4 Π state to levels v ′ = 11–16 by NO is measured as (8.80 ± 1.1) × 10 −11 cm 3 molecule −1 s −1 at 298 K where the error quoted is two standard deviations, and from measurements of the increased formation of high vibrational levels of NO(X) by the slow process we estimate a lower limit for the fraction of self-quenching collisions of NO A 2 Σ + ( v = 0) which lead to NO a 4 Π as 19%.